Development of a series of bis-triazoles as G-quadruplex ligands - Saleh, Maysaa; Laughton, Charles A.; Bradshaw, Tracey D.; Moody, Christopher J. (Royal Society of Chemistry, 2017)
Maintenance of telomeres – specialized complexes that protect the ends of chromosomes – is provided by the enzyme complex telomerase, which is a key factor that is activated in more than 80% of cancer cells, but absent in most normal cells. Targeting telomere maintenance mechanisms could potentially halt tumour growth across a broad spectrum of cancer types. Telomeric ends of chromosomes consist of noncoding repeat sequences of guanine-rich DNA. These G-rich ends can fold into structures called G-quadruplexes. Stabilization of G-quadruplexes by small binding molecules called G4 ligands can prevent telomerase enzyme from maintaining telomere integrity in cancer cells. G quadruplexes can exist in other parts of the genome too, especially within promoter sequences of oncogenes, and also be interesting drug targets. Here, we describe the development of a new series of novel bis-triazoles, designed to stabilize G-quadruplex structures selectively as G4 ligands. FRET assays showed two compounds to be moderately effective G4 binders, with particular affinity for the quadruplex formed by the Hsp90a promoter sequence, and good selectivity for G-quadruplex DNA vs. duplex DNA. However, CD spectroscopy failed to provide any information about the folding topology of the human telomeric G-quadruplex resulting from its interaction with one of the ligands. All the new ligands showed potent cell growth inhibitory properties against human colon and pancreatic cancer cell lines, as evidenced by the MTT assay; notably, they were more potent against cancer cells than in fetal lung fibroblasts. Docking studies were performed to rationalize the affinity of these ligands for binding to the telomeric parallel G-quadruplex DNA.